Perancangan Aplikasi Penggajian Student Labor Di Departemen Perpustakaan Universitas Advent Indonesia Menggunakan Rfid Berbasis Web - Raymond Maulany; Dina Yosephine Simanjuntak (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2017)
Technology is a part of human life today in support of daily activities and as a tool used to facilitate the work. One example that is experiencing problems in the field of technology, namely Advent Indonesia University on payroll student labor which is still done manually. The design that I have done is build an application using PHP and HTML programming language and MySQL database 2015. The procedure is designed to bring student KTM (Student Identity Card) to RFID Reader, then RFID Reader will read the identity of the card if it is registered, and put it into database. This research is done so that student labor can be easy to do attendance and receipt of salary every month. At run time, this application can save data to MySQL 2015 database that has been created. The author hopes that in the future this system can be developed so that this application can function better and more complete again.